Sleep: population epidemiology and concordance in Australian children aged 11–12 years and their parents. (4th July 2019) - Matricciani, Lisa; Fraysse, Francois; Grobler, Anneke C; Muller, Josh; Wake, Melissa; Olds, Timothy
Abstract : Objectives: To describe objectively measured sleep characteristics in children aged 11–12 years and in parents and to examine intergenerational concordance of sleep characteristics. Design: Population-based cross-sectional study (the Child Health CheckPoint), nested within the Longitudinal Study of Australian Children. Setting: Data were collected between February 2015 and March 2016 across assessment centres in Australian major cities and selected regional towns. Participants: Of the participating CheckPoint families (n=1874), sleep data were available for 1261 children (mean age 12 years, 50% girls), 1358 parents (mean age 43.8 years; 88% mothers) and 1077 biological parent–child pairs. Survey weights were applied and statistical methods accounted for the complex sample design, stratification and clustering within postcodes. Outcome measures: Parents and children were asked to wear a GENEActive wrist-worn accelerometer for 8 days to collect objective sleep data. Primary outcomes were average sleep duration, onset, offset, day-to-day variability and efficiency. All sleep characteristics were weighted 5:2 to account for weekdays versus weekends. Biological parent–child concordance was quantified using Pearson's correlation coefficients in unadjusted models and regression coefficients in adjusted models. Results: The mean sleep duration of parents and children was 501 min (SD 56) and 565 min (SD 44), respectively; the mean sleep onset was 22:42 and 22:02, the mean sleep offset was 07:07 and 07:27, efficiency was 85.4% and 84.1%, and day-to-day variability was 9.9% and 7.4%, respectively. Parent–child correlation for sleep duration was 0.22 (95% CI 0.10 to 0.28), sleep onset was 0.42 (0.19 to 0.46), sleep offset was 0.58 (0.49 to 0.64), day-to-day variability was 0.25 (0.09 to 0.34) and sleep efficiency was 0.23 (0.10 to 0.27). Conclusions: These normative values for objective sleep characteristics suggest that, while most parents and children show adequate sleep duration, poor-quality (low efficiency) sleep is common. Parent–child concordance was strongest for sleep onset/offset, most likely reflecting shared environments, and modest for duration, variability and efficiency.